Seeing destinations through short-form videos: Implications for leveraging audience involvement to increase travel intention - Han, Jiayu; Zhang, Gege; Xu, Shaogui; Law, Rob; Zhang, Mu (Frontiers in Psychology, 2022)
Short-form travel videos are popular, but the process of audience involvement while watching remains unclear. This study explores audience involvement along with expressions of travel intention and introduces the concepts of destination image and psychological distance to construct a structural model. A total of 487 questionnaires were used for structural equation model testing. Results show that audience involvement has a positive impact on the destination’s cognitive and affective image, ultimately leading to travel intention. Meanwhile, the destination’s cognitive and affective image play a partial mediating role between the influencing mechanisms. Moreover, psychological distance has a negative moderating effect between audience involvement and travel intention, and on audience involvement and cognitive image. However, it has no significant moderating effect on both audience involvement and affective image. The results provide a broader research perspective for the development of short-form travel videos and provide important implications for destination marketing.